EFISIENSI REMOVAL BAKTERI PADA FILTER AIR PAYAU DENGAN MEDIA KARBON AKTIF - Rahmayanti, Ardhana; Hamidah, Laily Noer (Journal of Research and Technology, 2019)
Seawater intrusion causes groundwater in coastal areas to be brackish, so it requires special processing to remove salt levels in raw water so that the water becomes tasteless. In addition to salinity, the presence of bacteria in water can cause disease if consumed without proper processing. Brackish water treatment called desalination can be done by ion exchange using an activated carbon filter. The purpose of this study was to determine the efficiency of the performance of brackish water processing filters in setting aside water quality parameters in the form of: coli bacteria and total bacteria expressed in the Total Plate Count (TPC). The filtration reactor is made using filter media in the form of activated charcoal (20cm), silica sand (15cm), zeolite (15cm), and gravel (10cm). laying the reactor upright and tilted 45 degrees. The results showed that the reactor filter was effective in reducing coli bacteria and total bacteria in raw water up to 100% and 97%, respectively, although it did not meet drinking water quality standards PERMENKES No.492 / Menkes / Per / IV / 2010. Both reactor variations have performance effectiveness that is not significantly different in processing raw water, but overall reactors with upright variations have better performance.